Penerapan Model Pembelajaran Role Playing dalam Meningkatkan Hasil Belajar Siswa pada Materi Pernikahan dalam Tinjauan Hukum Islam Siswa Kelas XII MIPA 1 SMA NEGERI 2 Sigli Tahun Ajaran 2020/2021 - Suhadi Suhadi (TANJAK, 2022)
This classroom action reseach aims to: (1) determine the improvement of student learning outcomes; (2) knowing teacher activities, dan (3) knowing student activities in applying the role playing learning model to marriage material in a review of Islamic law in class XII MIPA 1, with the focus of the reseach on increasing student achievement on the subject of marriage in a review of Islamic law by applying the role playing learning model. The reseach design used is Classroom Action Reseach, which is carried out in an integrated and systemic manner in stages, namely planning, action, observation, and reflection. Int the first cyclye, the average student learning outcomes on the subject of marriage in the Islamic law review was 56% with a sufficient category. In the second cycle the average student achievement on the subject of marriage in the Islamic law review was 86% with a good category. The increase in the average score of students in the subject of marriage in Islamic law review is 86%-56%=30%. Thus, the result of this study indicate that the application of the role playing learning model can improve student learning outcomes on marriage in the Islamic law review class XII MIPA 1 at SMAN 2 Sigli in the 2021/2022 academic year.